2015
DOI: 10.6060/mhc140929s
|View full text |Cite
|
Sign up to set email alerts
|

Pentakis-Amidothiacalix[4]arene Stereoisomers: Synthesis and Effect of Central Core Conformation on Their Aggregation Properties

Abstract: New monosubstituted pentakisthiacalix [4]arenes in three different configurations (cone, partial cone and 1,3-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Several approaches to the synthesis of multicyclophanes based on thiacalixarene [20,21], pillararene [22], and of hybrid structures containing both fragments [23] in high yields have been developed previously in our group. It was shown that synthesized multicyclophanes are capable of forming stable supramolecular associates [20,21] and also can participate in oxidative polymerization reactions with supramolecular assistance [23]. TREN as a convenient platform for the design of anion receptors and sensors [24,25] has been chosen as a core of the synthesized multicyclophane.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches to the synthesis of multicyclophanes based on thiacalixarene [20,21], pillararene [22], and of hybrid structures containing both fragments [23] in high yields have been developed previously in our group. It was shown that synthesized multicyclophanes are capable of forming stable supramolecular associates [20,21] and also can participate in oxidative polymerization reactions with supramolecular assistance [23]. TREN as a convenient platform for the design of anion receptors and sensors [24,25] has been chosen as a core of the synthesized multicyclophane.…”
Section: Introductionmentioning
confidence: 99%
“…Additional control of the purity of compounds and monitoring of the reaction were carried out by thin-layer chromatography using Silica G, 200 µm plates, UV 254. 4a-b, 5a-d, 6a-d Compounds 1 and 2 were synthesized according to published procedures [44][45][46]. Compounds 3a and 3b were synthesized according to published procedures.…”
Section: Chemistrymentioning
confidence: 99%
“…249 °C, 248.8 °C. [11] MALDI-TOF MS m/z C 45 H 50 O 10 : calculated 750. Pillar [5]arenes 3-7 were synthesized by literature method.…”
Section: Synthesesmentioning
confidence: 99%
“…[1][2][3][4][5][6] As a rule, a key role in these processes is played by macrocyclic compounds. [7][8][9][10][11][12][13] Depending on the size of the cavity, they are able to form host-guest systems, [14][15][16] leading to the formation of various supramolecular assembles.…”
Section: Introductionmentioning
confidence: 99%